2004
DOI: 10.1897/03-520
|View full text |Cite
|
Sign up to set email alerts
|

Maternal transfer of selenium in Alligator mississippiensis nesting downstream from a coal‐burning power plant

Abstract: Selenium (Se) is embryotoxic in many oviparous vertebrates, but little is known about maternal transfer of Se and its impact in reptiles. Over a four-year period, we collected three clutches of eggs of the American alligator (Alligator mississippiensis) from a single nest at a site contaminated with Se and compared egg and hatchling Se concentrations and clutch viability from this nest to nests downstream from the contaminated site (two clutches from two nests) and at a reference site (two clutches from two ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…In the literature, studies on the maternal transfer of Se for reptiles are well documented (Nagle et al, 2001;Hopkins et al, 2004;Roe et al, 2004;Unrine et al, 2006), and present a strong relation between concentration in eggs and concentrations accumulated in female tissue, that is consistent with the results of the present study. Reptilian studies on the remaining elements examined in this study are generally lacking; the only available data come from monitoring studies that only provide contamination in freshly laid eggs, reflecting a potential contamination coming from a maternal transfer (Table 1).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the literature, studies on the maternal transfer of Se for reptiles are well documented (Nagle et al, 2001;Hopkins et al, 2004;Roe et al, 2004;Unrine et al, 2006), and present a strong relation between concentration in eggs and concentrations accumulated in female tissue, that is consistent with the results of the present study. Reptilian studies on the remaining elements examined in this study are generally lacking; the only available data come from monitoring studies that only provide contamination in freshly laid eggs, reflecting a potential contamination coming from a maternal transfer (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…In birds, amphibians and reptiles, eggs receive their initial burden with maternal transfer during egg formation (Nagle et al, 2001;Kubota et al, 2002;Roe et al, 2004;Hopkins et al, 2006). Early life stages of oviparous organisms seem to exhibit higher sensitivity to chemical contaminants than adults (Russell et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that both essential (e.g., Zn, Se, Cu, and Cr) and non-essential elements (e.g., Cd, Pb, and Hg) are deposited in reptile eggs through maternal transfer (Burger 2002;Guirlet et al 2008;Hopkins et al 2004;Roe et al 2004;Tryfonas et al 2006). In the current study, while concentrations of Cr, Cd, and Pb were low in most of the eggs, Cu was measured in all the eggs evaluated.…”
Section: Maternal Transfer Of Heavy Metalsmentioning
confidence: 99%
“…Transfer of metals (such as selenium and mercury) has been observed in some species (e.g., Roe et al 2004), but most attention has focused on persistent synthetic compounds, particularly halogenated compounds such as PCBs and some pesticides. These compounds have received intensive study because their lipophilic properties provide a route of transfer from a female's stored lipids or proximate diet to offspring through yolk or milk, they have a propensity to accumulate to high concentrations in prey items and in female tissues prior to reproduction, and their use and release into the global environment is long-standing, ongoing, and intensive.…”
Section: Physiological and Reproductive Traits And Risks Of Contaminamentioning
confidence: 99%